СТАТИСТИКА РЕКОМБИНАЦИИ НЕРАВНОВЕСНЫХ НОСИТЕЛЕЙ ДЛЯ ПОЛУПРОВОДНИКОВ С ПАРНЫМИ РЕКОМБИНАЦИОННЫМИ КОМПЛЕКСАМИ, АКТИВНОСТЬ КОТОРЫХ СНИЖАЕТСЯ В ПРОЦЕССЕ ВОЗБУЖДЕНИЯ - Лейдерман, А.Ю.; Рахмонов, У.Х.; «Физика, Физико-технический институт НПО; Утениязов, А.К.; Уктамова, М.К.; Нсанбаев, М.Т. (SCIENCE and SOCIETY, 2020)
In the article recombination rate of non-equilibrium carriers is calculated for a semiconductor model with a pair recombination complex, the activity of which decreases during excitation. It is shown that the dependence of the electron capture coefficient on the first level on the filling of the second level leads to a decrease in the recombination rate even in the case of low inertia of the recombination processes, when the expression for the recombination rate is similar to the classical Shockley-Read dependence.